Find the product mentally.
(ab + 3)(ab - 3)

Question

Asked 12/19/2014 11:11:21 AM

Updated 12/19/2014 11:30:23 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by alfred123 [12/19/2014 11:28:42 AM]

s

andrewpallarca|Points 47003|

Question

Asked 12/19/2014 11:11:21 AM

Updated 12/19/2014 11:30:23 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by alfred123 [12/19/2014 11:28:42 AM]

Rating

3

(ab + 3)(ab - 3)

= a^2b^2 - 3ab + 3ab - 9;

= a^2b^2 - 9;

= a^2b^2 - 3ab + 3ab - 9;

= a^2b^2 - 9;

Added 12/19/2014 11:29:31 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [12/19/2014 11:43:01 AM]

3

(r + s)^2

= (r + s) (r + s);

= r^2 + rs + rs + s^2;

= r^2 + 2rs + s^2

= (r + s) (r + s);

= r^2 + rs + rs + s^2;

= r^2 + 2rs + s^2

Added 12/19/2014 11:30:23 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [12/19/2014 11:43:41 AM]

Find the product.
2y^2(3x + 5z) **Weegy:** x=9 (More)

Question

Not Answered

Updated 12/21/2014 6:51:43 AM

1 Answer/Comment

2y^2(3x + 5z)

= 2y^2*3x + 2y^2*5z

= 6xy^2 + 10zy^2

= 2y^2*3x + 2y^2*5z

= 6xy^2 + 10zy^2

Added 12/21/2014 6:15:56 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [12/21/2014 6:51:44 AM], Rated good by andrewpallarca

Find the product mentally.
(2m - 9)2

Question

Not Answered

Updated 12/19/2014 11:24:45 AM

2 Answers/Comments

(2m - 9)^2

= (2m - 9)(2m - 9);

= 4m^2 - 18m - 18m + 81;

= 4m^2 - 36m + 81

= (2m - 9)(2m - 9);

= 4m^2 - 18m - 18m + 81;

= 4m^2 - 36m + 81

Added 12/19/2014 11:24:06 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [12/19/2014 11:25:48 AM]

Find the product.
-2x a(-4x b - 2x 3 + 5x) **Weegy:** 2x a(-4x b - 2x 3 5x), The result is 2xa(-4bx-30x^2) **User:** Simplify 8 + 3{x - 2[x + 5(x + 3)]}. **User:** Find the product.
a 4(3a 2 - 2a + 1) **User:** Simplify p(p - q) - q(q - p). **User:** -4x 3 y 2(7xy 4) **Weegy:** -4x^3y^2(7xy^4) = -28x^4y^6 **User:** Find the product.
- y(2y 3 - 8) **Weegy:** - y(2y^3 - 8) (-y)(2y^3) + (-y)(-8) -2y^3 + 8y (More)

Question

Updated 12/20/2014 6:34:08 AM

2 Answers/Comments

-2x^a(-4x^b - 2x^3 + 5x)

= -2x^a*(-4x^b) + 2x^a*2x^3 - 2x^a*5x

= 8x^(a+b) + 4x^(a+3) - 10x^(a+1)

= -2x^a*(-4x^b) + 2x^a*2x^3 - 2x^a*5x

= 8x^(a+b) + 4x^(a+3) - 10x^(a+1)

Added 12/20/2014 6:32:22 AM

- y(2y^3 - 8)

= -y*2y^3 + 8*y

= -2y^4 + 8y

= -y*2y^3 + 8*y

= -2y^4 + 8y

Added 12/20/2014 6:34:08 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [12/20/2014 11:20:35 AM]

Simplify 7(n - p) + 5p.
User: Simplify 8 + 3{x - 2[x + 5(x + 3)]}. User: Multiply (5m 2 - 2m + 3)(3m - 4). **Weegy:** 3-3 = 0 **User:** Select the correct product.
(y + z)3 **Weegy:** What do you want me to do about your equation? **User:** Select the correct product
(y + z)3 **Weegy:** What do you want me to do about your equation? **User:** Select the correct product.
(x 2 + 4x + 8)(2x - 1) **Weegy:** (x^2 + 4x + 8)(2x - 1) = 2x^3 - x^2 + 8x^2 - 4x + 16x - 8; = 2x^3 + 7x^2 + 12x - 8 **User:** Select the correct product.
(6 - d)(d 2 - 5 + 3d) **Weegy:** Distributed Property
(6 - d)(d2 - 5 + 3d)
You can split it out if you find it's easier/less confuse to do.
6(d2 - 5 + 3d) - d(d2 - 5 + 3d)
6d2 - 30 + 18d - d3 +5d - 3d2
-d3 + 3d2 +23d-30 (Combine like terms) **User:**
(x2 + 4)(x2 - 4) **User:** (a + 3)(a - 2) **Weegy:** 4(3)^2 - 10(2) = 4(9) - 20; = 36 - 20; = 16 (More)

Question

Updated 12/20/2014 6:29:54 AM

4 Answers/Comments

(5m^2 - 2m + 3)(3m - 4)

= 5m^2*3m - 2m*3m + 3*3m - 5m^2*4 + 2m*4 - 3*4

= 15m^3 - 6m^2 + 9m - 20m^2 + 8m - 12

= 15m^3 - 26m^2 + 17m - 12

= 5m^2*3m - 2m*3m + 3*3m - 5m^2*4 + 2m*4 - 3*4

= 15m^3 - 6m^2 + 9m - 20m^2 + 8m - 12

= 15m^3 - 26m^2 + 17m - 12

Added 12/20/2014 6:25:52 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [12/20/2014 11:22:35 AM]

(y + z)^3

= (y + z)(y + z)(y + z)

= (y^2 + 2yz + z^2)(y + z)

= y^3 + 2y^2z + yz^2 + y^2z + 2yz^2 + z^3

= y^3 + 3y^2z +3yz^2 + z^3

= (y + z)(y + z)(y + z)

= (y^2 + 2yz + z^2)(y + z)

= y^3 + 2y^2z + yz^2 + y^2z + 2yz^2 + z^3

= y^3 + 3y^2z +3yz^2 + z^3

Added 12/20/2014 6:27:47 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [12/20/2014 11:24:15 AM]

(x^2 + 4)(x^2 - 4)

= x^2x^2 + 4x^2 - 4x^2 - 4*4

= x^4 - 16

= x^2x^2 + 4x^2 - 4x^2 - 4*4

= x^4 - 16

Added 12/20/2014 6:29:04 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [12/20/2014 11:25:21 AM]

(a + 3)(a - 2)

= a*a + 3*a - 2*a - 3*2

= a^2 + 3a - 2a - 6

= a^2 + a - 6

= a*a + 3*a - 2*a - 3*2

= a^2 + 3a - 2a - 6

= a^2 + a - 6

Added 12/20/2014 6:29:54 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [12/20/2014 11:26:18 AM]

(x2 + 3x + 1)(x2 + x + 2) **Weegy:** (x^2 + 3x + 1)(x^2 + x + 2) = x^4 + x^3 + 2x^2 + 3x^3 + 3x^2 + 6x + x^2 + x + 2; = x^4 + 4x^3 + 6x^2 + 7x + 2 **User:** (x2 + 4)(x2 - 4 **User:** (a + 3)(a - 2) **Weegy:** 4(3)^2 - 10(2) = 4(9) - 20; = 36 - 20; = 16 **User:** Select the correct product.
(y + z)3 **Weegy:** What do you want me to do about your equation? **User:** Find the product.
(n + 7)2
(More)

Question

Updated 12/21/2014 5:06:17 AM

4 Answers/Comments

(n + 7)^2

= (n +7)(n + 7)

= n^2 + 14n + 49

= (n +7)(n + 7)

= n^2 + 14n + 49

Added 12/20/2014 7:41:16 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [12/20/2014 11:28:35 AM]

(x^2 + 4)(x^2 - 4)

= x^2*x^2 + 4x^2 - 4x^2 - 4*4

= x^4 - 16

= x^2*x^2 + 4x^2 - 4x^2 - 4*4

= x^4 - 16

Added 12/21/2014 5:05:32 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [12/21/2014 5:11:05 AM], Rated good by andrewpallarca

(a + 3)(a - 2)

= a*a + 3*a - 2*a - 3*2

= a^2 + 3a - 2a - 6

= a^2 + a - 6

= a*a + 3*a - 2*a - 3*2

= a^2 + 3a - 2a - 6

= a^2 + a - 6

Added 12/21/2014 5:05:59 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [12/21/2014 5:11:30 AM], Rated good by andrewpallarca

(y + z)^3

= (y + z)(y + z)(y + z)

= (y^2 + 2yz + z^2)(y + z)

= y^3 + 2y^2z + yz^2 + y^2z + 2yz^2 + z^3

= y^3 + 3y^2z +3yz^2 + z^3

= (y + z)(y + z)(y + z)

= (y^2 + 2yz + z^2)(y + z)

= y^3 + 2y^2z + yz^2 + y^2z + 2yz^2 + z^3

= y^3 + 3y^2z +3yz^2 + z^3

Added 12/21/2014 5:06:17 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [12/21/2014 5:11:51 AM], Rated good by andrewpallarca

31,130,169

questions answered

victoria3

$107.11

Hearts 2,186 Views 8,712 Streams 112

phpmicro

$100.05

Hearts 2,016 Views 255,407 Streams 152

PranaMachine

$80.97

Hearts 1,653 Views 6,405 Streams 87

emdjay23

$72.45

Hearts 1,453 Views 133,028 Streams 112

maydj

$37.45

Hearts 1,103 Views 104,533 Streams 114

jezziem

$33.60

Hearts 825 Views 89,518 Streams 50

wallet.ro

$32.35

Hearts 789 Views 46,874 Streams 43

sacharyn

$30.30

Hearts 608 Views 59,795 Streams 52

There are no comments.